The Relationship between Job Satisfaction, Organizational Commitment and Leader-Member Exchange on Turnover Intention (Case Study in Head Office Employee of PT. WG) - Budi Wijaya; Bustanul Arifin Noer (IPTEK Journal of Proceedings Series, 2019)
The problem of turnover is experienced by many companies, including PT. WG. Head office of PT. WG has the highest rate of turnover among all locations of PT. WG. This study aims to determine the effect of job satisfaction, organizational commitment, and the relationship between leaders and the employees (Leader-Member Exchange - LMX) on employee turnover intention at the Head Office of PT. WG. It also aims to provide input to the management of PT. WG regarding things that need to be done to improve job satisfaction, organizational commitment, and LMX. This study uses a correlational method with primary data collected using a survey method in the form of a questionnaire. Collected data will be analyzed the suitability of the model with the hypothesis that has been proposed. Based on research that has been done, it was found that job satisfaction, organizational commitment, and LMX have a significant effect on turnover intention. Therefore PT. WG needs to pay attention to factors that influence job satisfaction and organizational commitment. In addition, leaders also need to pay attention to their relationships with subordinates. It is expected to reduce employee turnover intention at the Head Office of PT. WG.